For whom and by whom is glaciology? - Alexander A. Robel; Lizz Ultee; Meghana Ranganathan; Meredith Nash (Journal of Glaciology, 2024)
Glacier and ice sheet research is frequently justified on the basis of potential benefits to those communities that are most vulnerable to glacier change. In this glaciology research, funding priorities and communication to the broader public are strongly affected by the experiences and values of glaciology researchers. Using population data and newly available survey data from research organizations including glaciologists, we show that there is a substantial misalignment between the demographics of those who stand to benefit from glaciological research and those who produce glaciological knowledge. We discuss the potential negative consequences of this misalignment, which causes scientific research to be less effective, valuable and usable for communities. We conclude by outlining twenty evidence-based strategies that individuals and organizations can adopt to improve the recruitment and retention of a more representative group of scientists in glaciological research and encourage co-production with communities.